2017
DOI: 10.1038/s41598-017-09639-7
|View full text |Cite
|
Sign up to set email alerts
|

A neuropeptide, Substance-P, directly induces tissue-repairing M2 like macrophages by activating the PI3K/Akt/mTOR pathway even in the presence of IFNγ

Abstract: Macrophage polarization plays an important role in tissue damage and repair. In this study, we show that Substance-P (SP) can directly induce M2 polarization of inflammatory macrophages. SP induced the differentiation of GM-CSF-differentiated pro-inflammatory macrophages into alternatively activated phagocytic M2 like macrophages (M2SP) through direct activation of the PI3K/Akt/mTOR/S6kinase pathway and induction of Arginase-1, CD163, and CD206, all of which were nullified by pretreatment with the neurokinin-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 59 publications
3
69
1
Order By: Relevance
“…Engagement of CD163 initiates PI3k/AKT signaling, which, again, leads to IL10 secretion by the cell [24][25][26] . PBMΦ-0 and CBMΦ-0 showed no significant differences in IL-10 secretion after co-cultivation with EL (Fig.…”
Section: Cd163 Expression Correlates To Il10-secretion and Ho-1 Exprementioning
confidence: 99%
“…Engagement of CD163 initiates PI3k/AKT signaling, which, again, leads to IL10 secretion by the cell [24][25][26] . PBMΦ-0 and CBMΦ-0 showed no significant differences in IL-10 secretion after co-cultivation with EL (Fig.…”
Section: Cd163 Expression Correlates To Il10-secretion and Ho-1 Exprementioning
confidence: 99%
“…These neuropeptides directly act on various immune cells ( Figure 1). Substance P is known to be a proinflammatory neuropeptide that activates multiple immune cells, including T cells, macrophages, DCs, mast cells, eosinophils, and neutrophils (19)(20)(21). The functions of VIP and CGRP skew toward a Th2 cytokine-like phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the subtypes of M2 macrophages, M2a, is distributed in segmental glomerulosclerosis and tubular atrophy/interstitial fibrosis in IgA nephropathy patients and correlated with their severity (56). Interestingly, Lim et al demonstrated that SP is an environmental factor that determines the polarization of macrophages and mediates SP-specific M2 polarization with M2c function but with M2a markers (19). Therefore, further studies will be needed on the role and subtypes of SP-induced specific M2 macrophages in diverse kidney diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ischemia reperfusion injury (IRI), SP improves the injury by increasing MSC and endothelial progenitor cell (EPC) in the blood circulation and reducing TNFα (18). Furthermore, SP directly participates in the transition between M1 macrophages and M2 macrophages (19). However, SP expression has not been investigated in kidney disease, and whether SP has a beneficial effect on AKI is unclear.…”
Section: Introductionmentioning
confidence: 99%